An argument with neoliberalism: Australia's place in a global imaginary. (July 2014) - Weller, Sally; O'Neill, Phillip
This article argues that the uncritical application of the lens of neoliberalism closes off opportunities for more rigorous analysis of actually existing socio-economic change. We ask whether Australia's developmental trajectory over the last three decades can be described as neoliberalization and whether the outcome is a variety of neoliberalism. Instead of stitching together a story about variegated neoliberalism, we find an alternative narrative based around the notion of a developmental project more compelling. We document the spatial and political realities that have inhibited the roll-out of neoliberal ideas and practices in the Australian context. We think that instead of expanding the varieties of variegated neoliberalism to accommodate all manner of events and processes in all sorts of places, our task should be to recognize those instances where social, political, cultural or economic changes settle capitalism's contradictions in ways that diverge from neoliberal frameworks and expectations. Our central point is that the role of academic research is to explain the lived world and to develop abstractions to aid that explanation, rather than to design an abstraction (neoliberalism) and then fit the lived world to its contours.